Efektivitas pembelajaran dalam jaringan (online learning) selama wabah covid-19 pada peserta didik kelas v sekolah dasar - Vega Sandra Devi; Sandra Bayu Kurniawan; Peduk Rintayati (Didaktika Dwija Indria, 2021)
This study was conducted to reveal and describe the meaning of the effectiveness of online learning during the Covid-19 outbreak in fifth grade students of SD Negeri Wirotaman. The method used in this research is descriptive qualitative method with a phenomenological approach. The research was conducted using data collection techniques in the form of interview techniques, observation techniques, and documentation techniques. Sources of data in this study were students in grade V, teachers, and parents of students. The data in this study were processed using inductive data processing techniques according to Miles and Huberman. Based on the research results, the researcher found six variables that emerged, namely the online learning process, learning facilities, tutoring, students' understanding of the material, online learning constraints, and learning outcomes. Of the six variables found, the researcher has a relationship between one variable and another. Judging from the results of the study, the implementation of online learning for grade V SD Negeri Wirotaman was less effective. Online learning activities as a result of the Covid-19 outbreak caused obstacles that were felt by students. Students find it difficult to understand the subject matter, lack of concentration, are bored, and an unstable internet network.